2019
DOI: 10.1016/j.biomaterials.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

A lanthanide-peptide-derived bacterium-like nanotheranostic with high tumor-targeting, -imaging and -killing properties

Abstract: Nanostructures formed with bioactive peptides offer an exciting prospect in clinical oncology as a novel class of therapeutic agents for human cancers. Despite their therapeutic potential, however, peptide-based nanomedicines are often inefficacious in vivo due to low cargo-loading efficiency, poor tumor cell-targeting specificity and limited drug accumulation in tumor tissues. Here, we describe the design, via assembly of a p53-activating peptide termed PMI, functionalized PEG and fluorescent lanthanide oxyfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Linear peptides are conformationally disordered in aqueous solutions under their own steam and, consequently, tendentious to proteolysis. Conjugation of peptides with nanoparticles would improve steric hindrance against peptidase, resulting in the resistance to proteolysis 5 , 44 . We comparatively quantified the susceptibility of Pep-AuNPs and Pep-Au SNH to chymotrypsin using HPLC (Figure 3 E-G).…”
Section: Resultsmentioning
confidence: 99%
“…Linear peptides are conformationally disordered in aqueous solutions under their own steam and, consequently, tendentious to proteolysis. Conjugation of peptides with nanoparticles would improve steric hindrance against peptidase, resulting in the resistance to proteolysis 5 , 44 . We comparatively quantified the susceptibility of Pep-AuNPs and Pep-Au SNH to chymotrypsin using HPLC (Figure 3 E-G).…”
Section: Resultsmentioning
confidence: 99%
“…PC 10 P‐FITC, PC 10 ‐RBITC, and AC 10 ‐RBITC were prepared through the published procedures [24–26]. Briefly, 3 mg of polypeptide was dissolved in 1 mL carbonate‐bicarbonate buffer solution (0.1 M, pH 9), and 100 μL 1 mg/mL of FITC or RBITC was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies involving a mouse model with human colon cancer showed that the nanosystem is efficacious. More specifically, the nanorods can inhibit tumor growth and be easily mapped [211] . You et al prepared multifunctional nanosystems with sufficient cellular uptake, specific target and controlled release efficacy.…”
Section: Nanotheranostics Categories According To Their Chemical Natumentioning
confidence: 99%